2011
DOI: 10.1152/ajpheart.00200.2011
|View full text |Cite
|
Sign up to set email alerts
|

Myostatin from the heart: local and systemic actions in cardiac failure and muscle wasting

Abstract: A significant proportion of heart failure patients develop skeletal muscle wasting and cardiac cachexia, which is associated with a very poor prognosis. Recently, myostatin, a cytokine from the transforming growth factor-β (TGF-β) family and a known strong inhibitor of skeletal muscle growth, has been identified as a direct mediator of skeletal muscle atrophy in mice with heart failure. Myostatin is mainly expressed in skeletal muscle, although basal expression is also detectable in heart and adipose tissue. D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
71
0
5

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 107 publications
(79 citation statements)
references
References 101 publications
(137 reference statements)
3
71
0
5
Order By: Relevance
“…Although Myostatin is doubtless an inhibitor of skeletal muscle mass development, its role in muscle atrophy remains unclear. Indeed, in contrast to early observations highlighting a link between elevated levels of Mstn and low muscularity situations,41, 42, 43 recent studies showed a decrease of circulating Myostatin in conditions characterized by reduced skeletal muscle mass such as ageing, but without correlation between Myostatin levels and muscle mass 44, 45, 46. In agreement with our results, Breitbart et al .…”
Section: Discussionsupporting
confidence: 90%
“…Although Myostatin is doubtless an inhibitor of skeletal muscle mass development, its role in muscle atrophy remains unclear. Indeed, in contrast to early observations highlighting a link between elevated levels of Mstn and low muscularity situations,41, 42, 43 recent studies showed a decrease of circulating Myostatin in conditions characterized by reduced skeletal muscle mass such as ageing, but without correlation between Myostatin levels and muscle mass 44, 45, 46. In agreement with our results, Breitbart et al .…”
Section: Discussionsupporting
confidence: 90%
“…Proteolytic processing, secretion, proteolytic activation and inhibitory proteins (e.g. follistatin) can affect the activity of Mstn and other transforming growth factor- (TGF) factors (reviewed by Breitbart et al, 2011;Moustakas and Heldin, 2009). Moreover, TGF signaling is downregulated by inhibitory Smad, protein phosphatases and ubiquitin-dependent degradation of TGF receptors and Smads (reviewed by Liu and Feng, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…During pathological loading of the heart, the myocardium produces and secretes myostatin into circulation where it reaches skeletal muscles and inhibits their growth. 32 We have observed in heart failure rats that muscle atrophy was combined with changes in myostatin/follistatin expression. 22,33 Muscle disuse by bed rest can also contribute to protein catabolism.…”
Section: Imbalance Between Anabolic and Catabolic Processesmentioning
confidence: 95%